Character Association and Multivariate Analysis in Cashew (Anacardium occidentale L.) - Sethi, K.; Dash, M.; Tripathy, P. (International Journal of Bio-resource and Stress Management, 2020)
The cashew varieties tested in the experiment exhibited much variability among the vegetative and yield attributing traits. The heritability estimates ranged from 74.34% in total laterals to 97.44% in sex ratio indicating varied seasonal effect on character expression. High estimates of heritability (>60%) was obtained for all characters. The genetic gain was higher for all the traits except plant height, trunk girth, total laterals, flowering duration and shelling % (>20%) indicating the predominance of additive gene effects.Vegetative and flowering characters like trunk girth, canopy spread both in East-West and North-South direction, canopy area, nuts panicle-1and nuts m-2 were significantly positively correlated with nut yield both at genotypic and phenotypic levels. It is evident from both direct and indirect effects of the characters at phenotypic level that canopy spread (East-West), canopy area, trunk girth and nuts panicle-1would be of more value while selecting for yield. Multivariate analysis of tested cashew varieties revealed that crosses between genotypes of cluster V with genotypes of cluster VI may give rise to high yielding segregantsbecause of highest inter-cluster distance (441.034). Intercrossing of such genotypes involved in these clusters would be useful for generating variability for the respective characters, and their rational improvement for increasing the nut yield plant-1. The results also indicate that selection of genotypes with high cluster mean values for particular attribute could be used in the hybridization programme for improvement of that character.